Additive Manufacturing in Atomic Layer Processing Mode (Small Methods 5/2022). Issue 5 (16th May 2022) - Kundrata, Ivan; Barr, Maïssa K. S.; Tymek, Sarah; Döhler, Dirk; Hudec, Boris; Brüner, Philipp; Vanko, Gabriel; Precner, Marian; Yokosawa, Tadahiro; Spiecker, Erdmann; Plakhotnyuk, Maksym; Fröhlich, Karol; et al.
Abstract : Front Cover The invention of atomic‐layer additive manufacturing (ALAM): In ALAM, controlled surface chemistry is performed with spatially constrained flows of molecular precursors delivered to the substrate from a microfluidic nozzle. Each pass of the nozzle over any point of the substrate deposits one monolayer of solid. Repeated passes allow for direct patterning deposition of functional materials with Angström vertical resolution. This work by Julien Bachmann and co‐workers can be found in article number 2101546 .